State Capture and Collective Action - Capussela, Andrea Lorenzo (Journal of Regional Security, 2022)
A promising approach to analyse the phenomena usually described as ‘state capture’ may be drawn from the literature on ‘institutions’, ‘social orders’, and the ‘collective action prob- lem’. ese studies seem broader and more theoretically persuasive than the literature that con- nes itself to the notion of ‘state capture’, and this is especially true in respect of the Balkans, in whose societies it is often hard to draw a ne line between the ‘captured’ state and its ‘captors’. Seen through the lens of those strands of literature, the phenomena usually described as state capture appear to be more widespread than is currently assumed, as they also surface in advan- ced democracies, and behind them typically lie collective action problems, which prevent the public interest from imposing itself over special interests.
Keywords: state capture; collective action; social orders; institutions